Qiro'ah Learning Through Al 'Arobiyatu Linnasyiin as a Learning Resource for Bahrul Maghfiroh Malang Islamic Boarding School Students - Nidhom, Moch (Maliki Interdisciplinary Journal, 2024)
This study describes Qiro'ah Learning through Al 'Arobiyatu Linnasyiin as a learning resource for students of the Bahrul Maghfiroh Islamic Boarding School malang. The purpose of this study is to decrypt how effective the learning of maharah qiro'ah through the book of Al-Arabiyyah Linnasyiin and the responses or responses of students regarding the learning resources used. This research uses qualitative descriptive research methods by collecting data using observation techniques, interviews, and documentation. In the observation technique, the researcher observed the state of the learning environment of maharah qiro'ah Pondok Pesantren Bahrul Maghfiroh Malang in the form of a religious schools. In the interview technique, researchers interview students or students of ppbm diniyah madrasah starting from the first grade to the third grade. Meanwhile, in the documentation technique, researchers obtained data that some students found it difficult to learn independently using the book, because there were several factors that did not support students to study independently. As for the results of the interview, there are several differences in the opinions of the students about the learning of maharah qiro'ah, where the opinions have a side of differences that according to the researchers are caused by factors from the book used for learning and also factors that exist in the students themselves.